Pest categorisation of Malacosoma parallela - EFSA Panel on Plant Health (PLH); Claude Bragard; Paula Baptista; Elisavet Chatzivassiliou; Francesco Di Serio; Paolo Gonthier; Josep Anton Jaques Miret; Annemarie Fejer Justesen; Christer Sven Magnusson; Panagiotis Milonas; Juan A. Navas‐Cortes; Stephen Parnell; et al. (EFSA Journal, 2024)
Abstract The EFSA Panel on Plant Health performed a pest categorisation of Malacosoma parallela (Staudinger) (Lepidoptera: Lasiocampidae) for the territory of the European Union, following commodity risk assessments of Berberis thunbergii, Malus domestica, Prunus persica and P. dulcis plants for planting from Türkiye, in which M. parallela came to attention as of possible concern. M. parallela is commonly known as the mountain ring silk moth and is a polyphagous leaf‐eating pest in west‐central Asia, primarily feeding on deciduous trees and shrubs, and known to cause serious damage to Malus, Prunus, and Quercus species. It is found at a range of altitudes from 130 m to 3000 m although most common above 1000 m. It is a univoltine species. Eggs are laid in masses on twigs and branches in the summer and larvae hatch the following spring to feed on buds and fresh leaves. Host plants can be completely defoliated. Plants for planting and cut branches provide pathways for entry, especially if infested with egg masses. Host availability and climate suitability suggest that parts of the EU would be suitable for establishment. Adults can fly and the pest could spread naturally within the EU although adults only live for a few days. Faster and more extensive spread is therefore more likely via egg masses moved on plants for planting. The introduction of M. parallela into the EU could lead to outbreaks causing damage to deciduous trees and shrubs in forests and orchards. Phytosanitary measures are available to inhibit the entry and spread of this species. M. parallela satisfies all the criteria that are within the remit of EFSA to assess for it to be regarded as a potential Union quarantine pest.